Intracellular metabolic pathway distribution in diatoms and tools for genome-enabled experimental diatom research - Gruber, Ansgar; Kroth, Peter G. (My University, 2017)
Diatoms are important primary producers in the oceans and can also dominate other aquatic habitats. One reason for the success of this phylogenetically relatively young group of unicellular organisms could be the impressive redundancy and diversity of metabolic isoenzymes in diatoms. This redundancy is a result of the evolutionary origin of diatom plastids by a eukaryote-eukaryote endosymbiosis, a process that implies temporary redundancy of functionally complete eukaryotic genomes. During the establishment of the plastids, this redundancy was partially reduced via gene losses, and was partially retained via gene transfer to the nucleus of the respective host cell. These gene transfers required re-assignment of intracellular targeting signals, a process that simultaneously altered the intracellular distribution of metabolic enzymes compared with the ancestral cells. Genome annotation, the correct assignment of the gene products and the prediction of putative function, strongly depends on the correct prediction of the intracellular targeting of a gene product. Here again diatoms are very peculiar, because the targeting systems for organelle import are partially different to those in land plants. In this review, we describe methods of predicting intracellular enzyme locations, highlight findings of metabolic peculiarities in diatoms and present genome-enabled approaches to study their metabolism.This article is part of the themed issue 'The peculiar carbon metabolism in diatoms'.
Keywords: 570